Osteoporosis as a candidate for disease management: Epidemiological and cost-of-illness considerations - Torgerson, D; Cooper, C (1998)
Osteoporosis constitutes a major public health problem through its association with fractures at several skeletal sites, most notably the hip, wrist and vertebra. The lifetime risk of hip fracture in White women and men in the UK from age 50 years is 14% and 3%, respectively. These fractures account for considerable mortality, morbidity and healthcare expenditure. Methods of measuring bone density provide useful clinical tools for the assessment of future fracture risk, and a number of preventive and therapeutic strategies are now available to retard bone loss and reduce the incidence of fracture. The most cost-effective use of these pharmacological agents has become a focus for health economic research in osteoporosis. Such research will better define the setting in which various approaches to prevention and treatment are most effective.